2002
DOI: 10.1016/s0736-0266(01)00130-9
|View full text |Cite
|
Sign up to set email alerts
|

The spatiotemporal expression of TGF‐β1 and its receptors during periosteal chondrogenesis in vitro

Abstract: Transforming growth factor-pl (TGF-PI) has been shown to stimulate chondrogenesis in periosteal explants cultured in agarose suspension. TGF-Ps exert their cellular effects through a heteromeric cell membrane receptor complex consisting of TGF-P type I and type I1 receptors. In this study, the spatial and temporal expressions of the type I receptor (TPR-I), type I1 receptor (TPR-11) and endogenous TGF-P1 in periosteal explants cultured in vitro were examined using reverse transcription polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 56 publications
3
21
0
2
Order By: Relevance
“…This finding is further supported by the observation that TGF-β1 treatment and cyclic compressive loading promoted TGF-β1 gene expression in rabbit BM-MSCs. The effects of TGF-β1 treatment on the endogenous TGF-β1 gene expression found in this study were consistent with a recent finding, which showed that the TGF-β1 gene expression of rabbit periosteal explants increased after the TGF-β1 treatments of 7 and 42 days [26]. Previous studies have also demonstrated that mechanical loading can promote TGF-β1 production in cell cultures [32] and tissues [33,34].…”
Section: Compressive Loading and Chondrogenesissupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is further supported by the observation that TGF-β1 treatment and cyclic compressive loading promoted TGF-β1 gene expression in rabbit BM-MSCs. The effects of TGF-β1 treatment on the endogenous TGF-β1 gene expression found in this study were consistent with a recent finding, which showed that the TGF-β1 gene expression of rabbit periosteal explants increased after the TGF-β1 treatments of 7 and 42 days [26]. Previous studies have also demonstrated that mechanical loading can promote TGF-β1 production in cell cultures [32] and tissues [33,34].…”
Section: Compressive Loading and Chondrogenesissupporting
confidence: 93%
“…The TGF-β1 gene expression was also evaluated, since TGF-β1 treatment was shown to promote its gene expression in MSCs that resided in rabbit periosteal grafts [26]. Since compressive loading can transiently modulate the chondrocyte biosynthesis of cartilage-specific macromolecules, a set of specimens (n = 36: four groups per rabbit per time period × 3 rabbits × 3 time periods) were cultured in serum-free medium for 5 extra days after experimentation to account for the transient effects.…”
Section: Dynamic Unconfined Compression Testsmentioning
confidence: 99%
“…The periosteum was left in situ in order to contribute quantitatively and qualitatively to the regeneration process. Indeed, its release from the bone surface triggers the proliferation of the mesenchymal progenitors from its cambium layer [24,28] as well as the emission of growth factors which recruit precursor cells from the neighbour tissue and orientate their differentiation [13,22,29]. Thus, the regenerative process lead to the production of different skeletal elements: bone cartilage or fibrous tissue, according to the environmental variables [3].…”
Section: Discussionmentioning
confidence: 99%
“…Positive controls were cultured in growth media containing transforming growth factor beta (TGF-b) (Sigma, St. Louis, MO) (10 mM). TGF-b has been determined to influence chondrocyte differentiation and proliferation, is abundant in articular cartilage, and has been shown to stimulate chondrogenesis in vitro [10,11].…”
Section: Culture and Flow Cytometrymentioning
confidence: 99%